Monoclonal antibody-based immunofluorescence microscopy for the rapid identification of Burkholderia pseudomallei in clinical specimens. - Tandhavanant, S; Wongsuvan, G; Wuthiekanun, V; Teerawattanasook, N; Day, N; Limmathurotsakul, D; Peacock, S; Chantratita, N (2013)
The diagnosis of melioidosis depends on the culture of Burkholderia pseudomallei, which takes at least 48 hours. We used a polyclonal-FITC-based immunofluorescence microscopic assay (Pab-IFA) on clinical samples to provide a rapid presumptive diagnosis. This has limitations including photobleaching and batch-to-batch variability. This study evaluated an IFA based on a monoclonal antibody specific to B. pseudomallei (Mab-IFA) and Alexa Fluor 488. A diagnostic evaluation was performed on a prospective cohort of 951 consecutive patients with suspected melioidosis. A total of 1,407 samples were tested. Test accuracy was defined against culture as the gold standard, and was also compared against Pab-IFA. A total of 88 samples from 64 patients were culture positive for B. pseudomallei. The diagnostic sensitivity and specificity of the Mab-IFA was comparable to the Pab-IFA (48.4% versus 45.3% for sensitivity, and 99.8% versus 98.8% for specificity). We have incorporated the Mab-IFA into our routine practice.